Hakikat Peserta Didik Dalam Pendidikan Islam - Alihan Satra; Artisya Wulan Dini; Shofiani Januarsi Putri Raulih (Advances In Education Journal, 2025)
This article examines the nature of learners in Islamic education by highlighting their inherent potential, including fitrah, intellect, and spirituality, which must be developed holistically. Learners are viewed as active subjects who possess awareness, intention, and responsibility in the learning process. Islamic education emphasizes balanced intellectual, emotional, social, and spiritual development to shape the ideal human being (insan kamil). Understanding the nature of learners is essential for designing Islamic education that remains relevant to contemporary needs.